PERLINDUNGAN HUKUM BAGI KREDITUR TERHADAP KREDIT MACET DENGAN JAMINAN HAK TANGGUNGAN MELALUI SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN - , Parbantoro Danardono, S.H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tesis study is titled \"Legal Protection Against Lenders For Bad Credit Mortgage Granting Power of Attorney Charging Through Mortgage\", aims to understand the rule of law in applying the provisions of laws - laws against bad loans with collateral Mortgage via Impose Rights Attorney dependents, as well as to find out the problems that arise, factors - factors causing them and step - step in the implementation of the settlement of credit in this case the creditor to the debtor. This research is normative, the research supported by the empirical research literature that refers to a field study to obtain primary data. Studies conducted by the research literature documents laws - laws, as well as field research through interviews with informants. The data is then analyzed qualitatively with descriptive methods and purposes a descriptive analysis of the research results. Based on the analysis it can be concluded that legislation in this regard that regulates credit guarantee in the form of mortgage has not been implemented as it should be and have not been able to provide legal certainty for creditors. This is due to the economic competition between banks so that in applying the provisions against these loans the banks make allowances - allowances to customers, in addition to the lack of regulations on credit - credit that regulated which guarantee a Letter of Authorization to Impose Mortgage principal agreement ends, particularly for the provision of credit under the provisions of 50 million of general applicability. With regard to signing a blank blank, it is clearly a violation of the laws made by the Notary / PPAT and the bank as a lender which can result in a credit agreement with Mortgage guarantee null and void.